Answer:
u1 = \frac{(m1+m2)v}{m1}
Step-by-step explanation:
In a perfectly elastic collision,the bodies move together with a common velocity after collison.
let m1 represent the mass of body 1
m2 for mass of body 2
u1 is velocity of moving ball before collision
u2 is velocity of stationary ball before collision
v represents the common velocity of both bodies after collision.
u2=0, (body 2 is stationary)
we will substitute these variables into the formula
m1u1 + m2u2 =(m1+m2)v
m1u1 + m2 * 0 = (m1+m2)v
m1u1 = (m1+m2)v
u1 = \frac{(m1+m2)v}{m1}